A prism of the educational utopia: the East Asian Educational Model, reference society, and reciprocal learning: Comparing high-performing education systems: understanding Singapore, Shanghai, and Hong Kong, by Charlene Tan, Oxon, Routledge, 2018, 270 pp., 12.60 (paperback), ISBN 978-0815375920. Issue 6 (2nd November 2021) - Zhu, Gang
ABSTRACT: This paper discusses the emergence of the new global educational governance characterized by 1) global educational reform movement, 2) the active participation of the international organizations in global educational policy making, and 3) the emerging performative culture. Against this background, this article contextualizes the East Asian Educational Model (Shanghai, Singapore, and Hong Kong) and its operation mechanism by appropriating the Confucian habitus and educational harmonization. Then this study compares the EAEM, the high performing educational system, and the representative global fourth-way countries by interrogating the underling binary—new orientalism vs. reciprocal learning. Finally, this paper draws some implications by learning from these different educational systems.